Konsep Islam Wasathiyah dan Paham Keagamaan Muhammadiyah - Abdul Rozak Ali Maftuhin; Moh. Nurhakim (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The rise of religious extremism, intolerance, and liberalism highlights the urgent need for a moderate Islamic perspective that remains relevant to contemporary social dynamics. This study examines the concepts of Islam Wasathiyah, Progressive Islam (Islam Berkemajuan), and the Manhaj Tajdid and Tarjih within the Muhammadiyah perspective. Using a qualitative approach based on library research, the study analyzes books, journal articles, and other relevant academic sources to explore the theoretical foundations and practical implementation of these concepts. The findings indicate that Muhammadiyah’s understanding of Islam Wasathiyah is grounded in the principles of justice, balance, moderation, tolerance, consultation, reform, exemplary conduct, and responsible citizenship. These principles are embodied through the concept of Progressive Islam, which integrates Islamic propagation (da‘wah), renewal (tajdid), scientific advancement, and social engagement to promote civilizational progress. In addition, the Manhaj Tajdid and Tarjih provides a methodological framework that preserves the authenticity of Islamic teachings while responding rationally and contextually to evolving social realities. Consequently, Muhammadiyah offers a religious model that is moderate, progressive, adaptive, and relevant to contemporary challenges.